Active and passive smoking during pregnancy and ultrasound measures of fetal growth in a cohort of pregnant women. Issue 6 (12th January 2011) - Iñiguez, Carmen; Ballester, Ferran; Amorós, Rubén; Murcia, Mario; Plana, Alfredo; Rebagliato, Marisa
Abstract : Background: In utero tobacco exposure has been associated with adverse pregnancy outcomes but few studies have used longitudinal ultrasound measurements to asses the effects on fetal growth. The aim of this study was to examine the impact of active and passive smoking during pregnancy on fetal biometry in a cohort of Spanish women. Methods: Biparietal diameter (BPD), abdominal circumference (AC), femur length (FL) and estimated fetal weight (EFW) were evaluated in each trimester of pregnancy. Detailed information on smoking and potential confounders was assessed by questionnaire. SD scores were calculated from longitudinal growth curves adjusted for gestational age and potential determinants of growth. Size was assessed by means of unconditional SD scores at 12, 20, 32 and 38 weeks of pregnancy, while growth between these points was assessed by means of conditional SD scores. The association between smoking and fetal growth was investigated by regression models and adjusted for sociodemographic and lifestyle-related variables. Results: Maternal smoking was inversely associated with size of all parameters at weeks 32 and 38 and with growth in 20–32, 12–32 and 12–38 week intervals. In 32–38 weeks the effect was significant for AC and EFW. Environmental tobacco smoke (ETS) exposure was inversely associated with growth in BPD in all the intervals except 32–38 weeks. Conclusions: Active smoking during pregnancy was associated with a reduction in BPD, AC, FL and EFW from mid-gestation. ETS adversely affected BPD from early pregnancy.